On-farm Agro-meteorological evaluation of late sown wheat (Triticum aestivum) under irrigated agro-ecosystem of Upper Indo-Gangetic Plains - SHAMIM, M; PANWAR, A S; RAVISANKAR, N; JAT, PC; PRUSTY, A K; SINGH, M P; KASHYAP, POONAM; VERMA, NISHA; DATT, SHIV; ANSARI, M A; KUMAR, SUNIL (The Indian Journal of Agricultural Sciences, 2021)
In Indo-Gangetic Plains (IGP, 18 mha geographical area), wheat (Triticum aestivum L.) is a predominant crop grown in rabi. Improving the productivity of wheat in a rice-based farming system through a suitable cultivar in IGP is necessary to evaluate under the agro-ecological condition of IGP of India. A farmer’s participatory field experiment was studied at three villages Saunta, Sathedi and Bhangela situated in Khatauli block of Muzaffarnagar (Uttar Pradesh) under two crop environments (low rainfall and high temperature, LRHT and heavy rainfall and low temperature, HRLT) with four wheat varieties during rabi of 2017–18 and 2018–19. In this study we have evaluated the productivity in isolation as well as in combination of prevailing weather scenario (2017–18 and 2018–19) under irrigated agro-ecosystems of Western Plain Zone of Uttar Pradesh. Interaction studied between crop environments and varieties indicated that PBW-550 and PBW 658 registered higher grain yield of 5514 and 5475 kg/ha, respectively than farmers practice (PBW-226, 4659 kg/ha) and DBW-90 (4647 kg/ha) in LRHT. However, under HRLT, PBW-658 performed better (5326 kg/ha) over other cultivars. Mean grain yield of all four cultivars were recorded significantly higher under LRHT with 5074 kg/ha compared to HRLT where mean grain yield was 4710 kg/ha. A highly significant (P=0.01) negative association was found between grain yield and monthly rainfall (except December month) and cumulative rainfall of the crop season (-0.322**). Prevailing mean monthly air temperature during grain filling to maturity phenophase was found to be positively associated with grain yield (r = -0.322*).